Pendampingan Koperasi Syariah Berbasis Mesjid: Companiment of Mosque-Based Sharia Cooperatives - Srisusilawati, Popon; Putra, Panji Adam Agus (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
This community service aims to develop economic activities that focus on the establishment of a mosque-based cooperative in RW 08 Antaapani Wetan Village to introduce the community’s sharia economy so that the economy becomes better. The minimum achievement indicator is having an understanding of the basics of Islamic economics. The target of establishing a mosque-based cooperative in RW 08 is the local Mosque Prosperity Council. The method used in this community service is using effective socialization methods to the community, training, and mentoring. The activities that will be carried out are empowering DKM by providing socialization, training, and mentoring for mosque-based cooperatives. Assistance is carried out until the end of the program implementation period and after the program ends.